Effectiveness of innovator’s disruptive-based socioscientific learning (Innova-DB2SL) to improve analytical thinking and entrepreneurial skills - Noris, M.; Sajidan, Sajidan; Saputro, Sulistyo; Yamtinah, Sri (International Journal of Innovative Research and Scientific Studies, 2025)
The study evaluates the INNOVA-DB2SL model’s efficacy in enhancing students’ analytical and entrepreneurial thinking skills, addressing the modern world’s need for critical thinking and creativity in science learning. The study uses a mixed methods approach, combining qualitative and quantitative data. It employs MANOVA for quantitative analysis and collects qualitative data from student and instructor perspectives. The effectiveness of the INNOVA-DB2SL model is tested using a pretest-posttest control group approach. The sample includes 99 Senior High Non-Boarding School students and 183 Senior High Boarding School students. The INNOVA-DB2SL model, which integrates Socioscientific Issues (SSI) and the Scientific Approach, significantly enhances analytical thinking skills, with an average score of 80.62. This surpasses the Scientific Approach, which scored the lowest, indicating its limitations in cultivating deep analytical thinking. The study also found variations in these skills across different schools, with women generally outperforming men in both analytical and entrepreneurial thinking skills. The SSI model had the highest average score, slightly surpassing INNOVA-DB2SL, and younger students, particularly 16-year-olds, exhibited stronger analytical and entrepreneurial thinking skills. These findings highlight the importance of selecting appropriate learning models for students’ academic and professional success.